Development of Mustahiq Empowerment Instruments - Candri Candri; Didin Nurul Rosyidin; Abdul Aziz (Ilmu Inovasi Nusantara, 2022)
This study aims to determine the process of developing the mustahiq empowerment instrument to measure the success of the productive zakat distribution model and to obtain an assessment instrument that meets valid and reliable criteria. This type of research is Research and Development. Development procedure In this study using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). In the first stage the researcher conducted a preliminary analysis, the second stage the researcher designed the instrument, the third stage the researcher developed and determined the instrument, the fourth stage the researcher distributed the instrument and the fifth stage the researcher analyzed the results by testing the validity and reliability. The results of this study indicate that the instrument is valid and reliable with a reliability level of 0.587. community empowerment instrument with a total of 35 instrument points and 4 indicators that have been tested to be valid and reliable